2015
DOI: 10.1186/s40249-015-0074-9
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary validation of the Brief COPE instrument for assessing coping strategies among people living with HIV in China

Abstract: BackgroundThe Brief COPE instrument has been utilized to conduct research on various populations, including people living with HIV (PLWH). However, the questionnaire constructs when applied to PLWH have not been subjected to thorough factor validation.MethodsA total of 258 PLWH were recruited from two provinces of China. They answered questions involving the scales of three instruments: the Brief COPE, the Perceived Social Support Scale, and the Perceived Discrimination Scale for PLWH. Confirmatory factor anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
65
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 65 publications
(39 reference statements)
10
65
0
1
Order By: Relevance
“…which was similarly reported in previous validation studies including the original Brief-COPE study (Charles S. Carver, 1997;García et al, 2018;Monzani et al, 2015;Su et al, 2015). Nevertheless, the developer of Brief-COPE reported that the exibility of the inventory encourage researchers to apply and test on different settings and population to extensively either using all the subscales or selectively use relevant scales in their research (Charles S. Carver, 1997).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…which was similarly reported in previous validation studies including the original Brief-COPE study (Charles S. Carver, 1997;García et al, 2018;Monzani et al, 2015;Su et al, 2015). Nevertheless, the developer of Brief-COPE reported that the exibility of the inventory encourage researchers to apply and test on different settings and population to extensively either using all the subscales or selectively use relevant scales in their research (Charles S. Carver, 1997).…”
Section: Discussionsupporting
confidence: 56%
“…Yusoff et al (2009) investigation on Malay version of Brief-COPE among adolescent in Malaysia, produced a nine factor model explaining 71.2% of the total variance. Su et al (2015) generated a six factor model on the Chinese version of Brief-COPE, which explained 55.5% of total variance. Reich, Costa-Ball, & Remor (2016) constructed a four factor (24-items) model of the Uruguayan version, and more recently, Gloria & Peña (2018) produced an eight-factor (24-items) model on the Chilean version.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Brief COPE is a reliable and abbreviated version of the longer COPE inventory, which has been used to assess frequency of behaviors for coping with chronic illnesses [ 37 – 39 ]. For this study, the questions were framed to assess coping specifically with HIV and taking ART.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, other different measurement models have been proposed. Cooper and collaborators [31] identi ed three general coping styles (Problem-focused, Emotion-focused, and Dysfunctional coping) while Meyer [32] grouped the 14 original subscales in two styles: Adaptive and Maladaptive coping (see also: [33]). We have adopted this latter partition.…”
Section: Brief-cope (Coping Orientation To the Problems Experienced)mentioning
confidence: 99%